Assessment of Women and Youth Friendliness of Climate Smart Agriculture and One Health Technologies Piloted in Ghana - Haleegoah, Joyce; Yeboah, Stephen; Adomako, Joseph; Amankwaa-Yeboah, Patricia; Frimpong-Anin, Kofi; Eyram Amengor, Natson; Dalaa, Mustapha Alasan; Damba, Osman T; Kyere, Reginal; Obeng, Faustina; Tepa-Yotto, Ghislain (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The study assessed gender and social inclusiveness of the CSA technologies disseminated using indicators such as labor requirement, cost, youth involvement, and women friendliness. The women's friendliness was assessed with indicators such as the drudgery associated with the technologies, their accessibility and affordability, the sociocultural appropriateness of the technologies, the implementation requirements, and the technology's potential to displace women and youth of their roles. The study used both focus group discussions (qualitative) and survey (quantitative) approaches. The results of the study largely showed that labor requirements for the technology packages for both male and female farmers were low. On the contrary, during FGD it was revealed that the cost of improved planting materials and associated technologies was considered high for all the value chains. Youth involvement and the friendliness of the CSA technologies to women were ranked high by participants. The requirements for implementation were low, and the technology was accessible and affordable not displacing women and youth in their roles. However, the yam technologies were not culturally inclusive in some ethnic groups due to cultural restrictions on women to cultivate yam. Generally, majority of farmers in the study considers the technologies had lower drudgery (65.04%), accessible (80.87%) and affordable (67.96%), socio-culturally appropriate (70.35%), lower implementation requirements (52.73%) and do not displace women and youth of their roles (75.4%). The results of this follow-up study indicate that, the CSA disseminated technologies were gender friendly and inclusive.